The relationship between food consumption and socio-economic status: evidence among British youths - Paola De Agostini (University of Essex, Institute for Social and Economic Research (ISER), 2005)
This paper investigates the relationship between nutrition and socio-economic status among British youths. It describes the dynamics of consumption over age and time using data from the British National Food Survey (NFS) covering the period 1975- 2000. Daily calories-age relationships for men and women are estimated by solving a non-linear least square model with a roughness penalty function approach. Focusing on young age groups, trends of consumption over the 25-year period of study and the cohorts effect have been explored across three classes of age. Finally, an exploration of specific trend variations in eating habits has been implemented controlling for income distribution.
Keywords: 330